Scaling up of sustainable soil management practices: some lessons from the hills of Nepal (Journal of Forest and Livelihood, 2024)
A study was conducted to assess the scaling up processes of soil management practices under maize based farming systems in Panchkhal and Sanga areas of Kavre district. The key objectives of the study are to analyze the scaling up processes and pathways of soil management practices in the case study areas and identify factors related to scaling up at different levels. Three principalquestions guiding the analysis were: a) what are the positive aspects of scaling up processes and how can these be built on? b) What are the problems being experienced and how can these be overcome? c) What is the influence of people's livelihood strategies and assets on the processes? Kavre is one of the 10 districts where Sustainable soil Management Programme (SSMP) ofHelvetas has helped local people in the adoption of innovative soil management practices integrated with various cash and subsistence crops. With SMP support and advice, services to farmers in these areas create awareness and build their institutions (CIs) provide extension services to farmers in these areas create awareness and build their institutional capacity onadopting innovative soil management practices. The goal of the project is to improve livelihoods of resource poor farmers.Data for the study were gathered from 29 households through interviews, two workshops with key informants at the community level and a workshop with CIs at district levels, and review of SSMP and partners' documented information on the subject. The research team also made transect visits through the area, and interviewed several staff of the collaborating institutions. Qualitativeanalysis (in terms of perceptions of respondents) as well as quantitative analysis of data was done at household, community and institutional levels.